2019
DOI: 10.1177/1937586719839229
|View full text |Cite
|
Sign up to set email alerts
|

The Hospital (Not So) Quiet Zone: Creating an Environment for Patient Satisfaction Through Noise Reduction Strategies

Abstract: Purpose: To determine whether using existing noise reduction strategies improves patients’ overall satisfaction level during hospitalization on an adult outpatient cardiology unit and to assess whether noise reduction strategies were effective to decrease the ambient noise for both staff and patient environments. Background: Excessive noise is a worldwide problem facing hospitals today. Noise has been proven to be detrimental to staff and patient well-being and hospital environment satisfaction levels. Interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…We can also use an anti-vibration soundproof floor mat underneath the compressor to reduce the transmission of noise and vibrations [ 85 ]). Additionally, closing the doors when operating is a simple and effective measure for noise reduction within a healthcare unit [ 86 ]. Other measures that might work at this direction are also reported, such as verbal and visual alarm reminders for staff, posting quiet signs for patients, and limiting electrical equipment through the waiting areas or the operational office [ 86 ].…”
Section: Options Of Sound Control Design In the Dental Officementioning
confidence: 99%
“…We can also use an anti-vibration soundproof floor mat underneath the compressor to reduce the transmission of noise and vibrations [ 85 ]). Additionally, closing the doors when operating is a simple and effective measure for noise reduction within a healthcare unit [ 86 ]. Other measures that might work at this direction are also reported, such as verbal and visual alarm reminders for staff, posting quiet signs for patients, and limiting electrical equipment through the waiting areas or the operational office [ 86 ].…”
Section: Options Of Sound Control Design In the Dental Officementioning
confidence: 99%
“…future solutions should be based on a careful assessment of each hospital environment, and designed with input from all stakeholders, particularly patients and families." Studying the overall soundscape will also be a part of evaluating the emotional well-being of the healthcare worker, as it has been shown that noise pollution leads to stress and burnout among healthcare staff (Topf, 2000;Walker & Karl, 2019).…”
Section: The Auditory World Of the Patientmentioning
confidence: 99%
“…Better understanding the overall soundscape in these spaces from a person-centered perspective will help hospital designers and administrators decide what sounds which should be minimized or eliminated. As Xyrichis et al (2018) explain, “patients and relatives are rarely involved in this research; they are seen as passive recipients of the hospital soundscape rather than active participants in its creation…future solutions should be based on a careful assessment of each hospital environment, and designed with input from all stakeholders, particularly patients and families.” Studying the overall soundscape will also be a part of evaluating the emotional well-being of the healthcare worker, as it has been shown that noise pollution leads to stress and burnout among healthcare staff (Topf, 2000; Walker & Karl, 2019).…”
Section: Emotional Design: Paying Attention To Sound Light and Colormentioning
confidence: 99%
“…The layout of patient care areas is intentionally designed to decrease or eliminate disruption of patient rest from noise; quiet hours promote rest and eliminate noisy distractions. Some organizations have included the use of visual "stoplight-style" system aids, such as the Yacker Tracker, to indicate when noise reaches a certain decibel level (Walker & Karl, 2019). Hospitals adhere to high standards of cleanliness to decrease the risk of nosocomial infections.…”
Section: Visionarymentioning
confidence: 99%